2008 8th IEEE International Conference on Automatic Face &Amp; Gesture Recognition 2008
DOI: 10.1109/afgr.2008.4813341
|View full text |Cite
|
Sign up to set email alerts
|

Bi-channel sensor fusion for automatic sign language recognition

Abstract: In this paper, we investigate the mutual-complementary functionality of accelerometer (ACC)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 12 publications
0
19
0
Order By: Relevance
“…Their experiments using 10 subjects demonstrate that it is preferable to add an accelerometer to a two-site sEMG system rather than a third electrode. Related to the context of prosthetic control, the integration of accelerometers and sEMG has also proven useful for sign language recognition [7], [8]. For example, the information fusion framework proposed by Zhang, Chen, Li, et al [8] classified 72 Chinese sign language words with more than 95% accuracy, largely due to the complementary nature of both modalities.…”
Section: Introductionmentioning
confidence: 99%
“…Their experiments using 10 subjects demonstrate that it is preferable to add an accelerometer to a two-site sEMG system rather than a third electrode. Related to the context of prosthetic control, the integration of accelerometers and sEMG has also proven useful for sign language recognition [7], [8]. For example, the information fusion framework proposed by Zhang, Chen, Li, et al [8] classified 72 Chinese sign language words with more than 95% accuracy, largely due to the complementary nature of both modalities.…”
Section: Introductionmentioning
confidence: 99%
“…There exist several sensor gloves designed for sign language translation. Kim et al [16], for example, applied a combination of a tri-axial accelerometer and an electromyogram (EMG) sensor for the recognition of seven words in German sign language. The sensors were attached on the arm and signals were transmitted wirelessly via Bluetooth.…”
Section: Introductionmentioning
confidence: 99%
“…The sensor-based techniques, especially wireless sensors [1,7,16], can provide users with enhanced mobility. The devices are usually more expensive and can be cumbersome in some cases.…”
Section: Introductionmentioning
confidence: 99%
“…Kim et al [10] proposed a system which combined sensor data from accelerometers and an Electromyogram (EMG) which was used to measure the electrical activity produced by the hand muscles. It was shown that the information added by the EMG greatly improved the recognition rate of signs.…”
Section: Fig22 Hand Gesture Experimental Setup With Four Electrodes mentioning
confidence: 99%